Contest Corner: The 2021 State Tournament of Mathematics Results - Flick, Michael; Kuchey, Debora (Ohio Journal of School Mathematics, 2022)
The article presents the top scores and statistics for student and schools for the Fall 2021 State Tournament of Mathematics.  Also presented are a sampling of problems from previous contests.